Genetic diversity using single nucleotide polymorphisms (SNPs) and screening for salinity tolerance in rice germplasm at reproductive stage - Barrera, Wilfredo B.; Dela Viña, Celia B.; Vispo, Naireen Aiza; Singh, Rakesh Kumar (Cambridge University Press, 2019)
Genetic diversity is a valuable asset for crop improvement. In this study, a total of 50 rice genotypes were screened for salinity tolerance at the reproductive stage using gravel-based hydroponics, soil, controlled mini-field and field methods. Different morpho-agronomic, physiological markers and tolerance indices were used to classify tolerant and susceptible genotypes. Our results showed high genetic variability in response of rice genotypes to salinity using different screening methods. The significant effect (P < 0.01) of salinity include increased Na+ sequestration in the flag leaf, increased unfilled grains (except for the field method) and reduced pollen fertility, total yield, panicle length and the average number of filled grains per panicle. Plant height (except for the soil method) and K+ ion concentration in the flag leaf were not significantly affected by salinity (P > 0.05). Genetic diversity analysis indicated that the germplasm evaluated exhibits moderate diversity (PIC ${\overline{\bf X}}$ = 0.2085). Cluster analysis using single nucleotide polymorphisms showed that the genetic make-up of rice germplasm somehow did not necessarily indicate their over-all tolerance or susceptibility to salinity. This study proved that the controlled mini-field method is the most advantageous among the screening methods while geometric mean productivity, stress tolerance index and yield index are the tolerance indices that can be classified as better predictors of salinity tolerance considering the yield potentials of the genotypes. The genotypes Nona Bokra and Mushkan 41 can be used for breeding in the future through low Na+:K+ ratio while Damodar and Bhura Rata 4-10 for breeding salt-tolerant cultivars with higher yield potentials.